Detection of the Brachyspina mutation in Uruguayan Holstein cows using real time PCR and melting curve analysis - Rodriguez,María Teresa Federici (2021)
ABSTRACT: Brachyspina syndrome (BS) is a rare monogenic autosomal recessive hereditary disorder of the Holstein Fresian breed caused by a deletion of 3.3Kb in the Fanconi anemia complementation group I (FANCI) gene on BTA-21, which leads to a frame-shift and premature stop codon. Some of the consequences of BS are the reduction of the fertility rate and milk production. This study developed a simple, sensitive, rapid cost- effective assay method based on real time PCR and melting curve analysis for the detection of BS carrier animals. Sixty-eight normal homozygous and four heterozygous carrier genotypes were detected and confirmed through traditional PCR- electrophoresis analysis. We concluded that the assay we have developed proved to be a reliable, highly precise and low-cost tool, which could be used to monitor the presence of the BS mutation in uruguayan Holstein breed.